2011
DOI: 10.1371/journal.pone.0020138
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Macrophage Chemotaxis by Aortic Extracts from Patients with Marfan Syndrome Is Related to Elastin Binding Protein

Abstract: Marfan syndrome is an autosomal dominantly inherited disorder of connective tissue with prominent skeletal, ocular, and cardiovascular manifestations. Aortic aneurysm and dissection are the major determinants of premature death in untreated patients. In previous work, we showed that extracts of aortic tissues from the mgR mouse model of Marfan syndrome showed increased chemotactic stimulatory activity related to the elastin-binding protein. Aortic samples were collected from 6 patients with Marfan syndrome and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 61 publications
3
28
0
Order By: Relevance
“…Aortic wall extracts of Marfan mice induced increased chemotaxis of macrophages in vitro, mainly induced by elastin binding protein, showing a chemotactic stimulatory activity of fibrillin-1fragments [11]. These results were recently confirmed in MFS patients' aortas [12]. Furthermore, macrophages found in the aortic wall of these mice are positive for certain matrix metalloproteinases, which are enzymes that contribute to the degradation of the extracellular matrix.…”
Section: Introductionmentioning
confidence: 67%
“…Aortic wall extracts of Marfan mice induced increased chemotaxis of macrophages in vitro, mainly induced by elastin binding protein, showing a chemotactic stimulatory activity of fibrillin-1fragments [11]. These results were recently confirmed in MFS patients' aortas [12]. Furthermore, macrophages found in the aortic wall of these mice are positive for certain matrix metalloproteinases, which are enzymes that contribute to the degradation of the extracellular matrix.…”
Section: Introductionmentioning
confidence: 67%
“…Although there was no inflammation or invasion by macrophages observed in one study of aneurysmal aorta of MFS [82], another report showed infiltration by macrophages and lymphocytes [88]. Consistent with this, fibrillin-1 fragments and extracts of the aortic wall of Fbn1 deficient mice and MFS patients can increase chemotaxis of macrophages [89,90]. An analysis of gene expression in MFS patients [91] found that inflammation was correlated with many clinical features of the condition.…”
Section: Fibrillin-1 Mutationsmentioning
confidence: 83%
“…Several groups propose that SMC apoptosis promotes aortic wall macrophage recruitment, 25 major sources of ECM-degrading enzymes, including the matrix metalloproteinases. 13,24,26 Although our laboratory has reported that MMPs participate in aneurysm development in Marfan Fbn1 C1039G/+ mice, 4 the absence of inflammatory cell infiltration suggests that apoptotic SMCs must contribute to early aneurysm development through an alternative mechanism.…”
Section: Discussionmentioning
confidence: 99%